GENOMIC EXPLORATION OF THE MST(-like) GENE FAMILY IN Mangifera indica: INSIGHTS INTO DEVELOPMENT AND STRESS RESPONSE - Mahmoud Kandeel; Mahmoud Kandeel (Journal of Animal and Plant Sciences, 2024)
Mangifera indica (M. indica) is a widely consumed fruit in tropical and subtropical regions. The Monosaccharide Transporter (MST) gene family plays a crucial role in sugar transport and stress response. This study investigates the MST(-like) gene family in M. indica to understand its genomic characteristics and role in fruit development and stress response. Comparative analysis with Arabidopsis thalianaidentified 28 MST(-like) genes in M. indica. Phylogenetic analysis and promoter region analysis were conducted. Gene expression was evaluated using Next Generation Sequencing (NGS) data, and qRT-PCR was used to validate responses to drought stress. MiSTP5 exhibited the highest up-regulation, while MiINT3 showed significant down-regulation. Promoter analysis revealed involvement in drought, salicylic acid signaling, and light responsiveness. Following drought stress, MiPLT5 and MiPLT6 gene expressions increased, while MiSTP5 and MiINT3 decreased over seven days. The identified MST(-like) genes are key to understanding the developmental processes and stress response in M. indica. These genes may serve as valuable markers for detecting stress, with potential applications in agriculture.
Keywords: Genomics Analysis; Mangifera indica; NGS; Phylogenetic Analysis